The influence of COVID-19 pandemic on college students’ academic performance and the construction of a learning ability warning system - Ren, Zengqiang; Du, Qiaoling (Frontiers in Public Health, 2024)
ObjectiveThis study explored the impact of prevention and control measures taken by Chinese universities on college students’ academic performance during the COVID-19 pandemic.ParticipantsThe sample includes 1,009 senior students, 1,140 junior and sophomore students, and 1,198 freshman students studying at a top university in China from 2012 to 2023.MethodsAnalysis of variance was used to analyze historical data, and a learning ability warning system based on probabilistic neural networks was further proposed.ResultsThere was a significant difference in student academic performance from 2019 to 2022 compared to historical data. Prevention and control measures such as school closures and online teaching have affected the academic performance of college students.ConclusionCOVID-19 has a negative impact on college students’ learning ability. It is necessary to establish a learning ability warning system to assist university management departments in formulating relevant policies to restore the learning ability of college students.